Composite MRI measures and short-term disability in patients with clinically isolated syndrome suggestive of MS. (April 2018) - Bommarito, Giulia; Bellini, Alessandro; Pardini, Matteo; Solaro, Claudio; Roccatagliata, Luca; Laroni, Alice; Capello, Elisabetta; Mancardi, Giovanni Luigi; Uccelli, Antonio; Inglese, Matilde
Background: The use of composite magnetic resonance imaging (MRI) measures has been suggested to better explain disability in patients with multiple sclerosis (MS). However, little is known about the utility of composite scores at the earliest stages of the disease. Objective: To investigate whether, in patients with clinically isolated syndrome (CIS), a composite MRI measure, rather than the single metrics, would explain conversion to MS and would better correlate with disability at baseline and at 1 year of follow-up. Methods: Corticospinal tract (CST), corpus callosum (CC) and optic radiation (OR) volume, fractional anisotropy (FA), and mean diffusivity (MD) values were measured in 27 CIS patients and 24 healthy controls (HCs). Z-scores of FA, MD, and tract volume measures were calculated in patients, based on the corresponding measures obtained from HCs, and then combined in a composite score for each tract. Correlations between Z-scores at baseline and both the Expanded Disability Status Scale (EDSS) at baseline and at follow-up (FU-EDSS) were investigated. Results: Only CST, CC, and OR composite scores as well as the CST volume were significantly associated with FU-EDSS ( p  = 0.005, p  = 0.007, p  = 0.020, and p  = 0.010, respectively). Conclusion: The combination of MRI measures rather than the individual metrics better captured the association between tissue damage in both the CC, OR and CST and short-term follow-up disability.